Impact of health education on women’s knowledge, attitude and practice regarding menopause in Karnataka - Javali, Shwetha; C., Kunhanam Lilly; K. V., Malathi; K. E., Pankaja; Ayilya, A. S.; Begum, Shaik Munira (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Menopause represents an important change in a woman’s life, frequently accompanied by various physical, emotional, and social alterations. In spite of its effects, numerous women, especially those in rural regions, do not have sufficient understanding and assistance. This study aimed to evaluate the impact of a health education program on knowledge, attitude, and practice (KAP) regarding menopause among women in Karnataka. Method: A total of 340 women aged between 35 and 65 years were selected to participate in the study through systematic sampling methods. The study encompassed both pre-menopausal and post-menopausal women, while individuals who were unavailable or opted not to participate were excluded from the analysis. Initial data were collected regarding demographic information, health history, and reproductive status. Subsequently, an educational intervention was implemented, focusing on the symptoms of menopause, management techniques, and healthy lifestyle practices. The assessment of knowledge, attitudes, and practices (KAP) levels occurred before and after the intervention using structured interview schedule. Results: At baseline, all participants exhibited inadequate knowledge regarding menopause. Following the intervention, only 7% retained a classification of poor knowledge, while 80% attained average knowledge and 13% achieved good knowledge. Positive attitudes increased from 22% to 74%, and negative attitudes declined from 78% to 26%. Instances of good practices improved from 7% to 36%, whereas instances of poor practices decreased from 93% to 64%. Notably, participation in yoga and meditation activities surged from 13% to 89%, alongside a significant enhancement in health-seeking behavior. Conclusion: The health education program proved highly effective in enhancing KAP related to menopause. However, the initially low awareness emphasizes the need for sustained community-based educational initiatives and continued research to support women through menopausal transition.